Meningkatkan Motivasi Belajar Siswa Melalui Penggunaan Media Window Movie Maker Dalam Materi Klasifikasi Makhluk Hidup - Dini Kurniani (FKIP UNIVERSITAS PAKUAN, 2015)
The aim of the study is to improve students’ motivation through the use of window movie maker media in living things classification on natural science subject of class VII at SMP 1 Babakan Madang, Bogor. The research used classroom action research design. The data was collected from the students’ achievement and observation notes. Based on the three cycles of the research, it is found that the students’ motivation which was very low (14,92%) before the research (pre-cycle) improved into adequate in the first cycle (49,76%) and it got higher in the second cycle (65,23%) and finally it became excellent in the third cycle (89,15%). Based on the research, it is suggested that teachers use attractive and communicative learning media so that the students are motivated to use them as one of the source for learning, not only teachers.